Optimizing DNA Extraction and Selecting Suitable Regions for Biodiversity Assessment: A Study on Shorea leprosula - Rachmat, Henti Hendalastuti; Yulita, Kusumadewi Sri; Dwiyanti, Fifi Gus; Susilowati, Arida; Arrofaha, Nawwall; Susila, Susila; Kamal, Irsyad; Siregar, Iskandar Zulkarnaen (Jurnal Manajemen Hutan Tropika, 2024)
The extraction method plays a crucial role in obtaining high-quality DNA samples, which is indispensable for various molecular biology techniques and analyses, enabling a deeper comprehension of genetic information and biological processes. The objectives of the study were: a) to optimize the chloroplast DNA extraction protocol by comparing modified CTAB methods and GeneAid for both leaf and wood samples of Shorea leprosula, a major commercial timber species, and b) to identify a suitable cpDNA region that exhibits variability and universality across taxa. Total DNA was analyzed by gel electrophoresis followed by Sanger sequencing to determine the amplification success. The results revealed that trnL intron, trnL-trnF, and trnG yielded readable sequences of the expected length (maximum 586 bp, 480 bp, and 908 bp, respectively), while the rps 16 intron failed to assemble a contig. The petL-psbE region provided long readability for reverse sequences (769 bp) but not for the forward sequence (195 bp). Higher successful DNA extraction was achieved from the leaves compared to the woods. The lower sequencing quality may be attributed to suboptimal primer design, the structural features of the regions resulting from extensive repetitive sequences, and the suboptimal condition of the extraction method in eliminating wood chemical compounds.